Comparison of plasma and vacuum corpuscular lenses by parameters determining their focusing strength - Ivanov, B.I. (Вопросы атомной науки и техники, 2002)
For three types of electrostatic lenses the focusing length is proportional, accordingly, to the second-, or first-, or half-power of the parameter representing the relation of a charged particle accelerating potential to a lens potential. Accordingly, for magnetic lenses the focusing length is proportional to the second-, or first-, or half-power of the parameter representing the relation of the particle kinetic momentum to the electromagnetic component of its canonical momentum.